Effects of Daily and Reduced Frequency Implementation of the Good Behavior Game in Kindergarten Classrooms. Issue 4 (July 2020) - Dadakhodjaeva, Kamila; Radley, Keith C.; Tingstrom, Daniel H.; Dufrene, Brad A.; Dart, Evan H.
An effective group contingency, the Good Behavior Game (GBG), has been implemented successfully with a wide range of age groups. However, improvements in student behavior are often not observed when the GBG is abruptly terminated, and research has yet to evaluate the effects of the GBG when the frequency of implementation is reduced. The purpose of the current study was to evaluate the effect of the GBG, implemented daily initially then on a less frequent schedule. The study utilized a multiple baseline design across three kindergarten classrooms to evaluate the effectiveness and maintenance of the GBG at reducing classwide and target student disruptive behavior (DB) and increasing classwide and target student academic engagement. Reduced Frequency data were collected while withholding implementation of the GBG. The results indicate that the GBG was highly effective in improving classwide behavior, which was maintained throughout the final Reduced Frequency phase in which the GBG was reduced in frequency, and moderately effective in improving target student behavior during both phases.